Comparative investigation of immediate effects on neuro-endocrine-immune complex of bioactive water Naftussya from layers Truskavets’, Pomyarky and Skhidnyts’a. Communication 1. Generic effects - Sydoruk, Nadiya O; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Sydoruk Nadiya O, Zukow Walery. Comparative investigation of immediate effects on neuro-endocrine-immune complex of bioactive water Naftussya from layers Truskavets’, Pomyarky and Skhidnyts’a. Communication 1. Generic effects. Journal of Education, Health and Sport. 2016;6(8):85-101. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59762 http://ojs.ukw.edu.pl/index.php/johs/article/view/3734 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. COMPARATIVE INVESTIGATION OF IMMEDIATE EFFECTS ON NEURO-ENDOCRINE-IMMUNE COMPLEX OF BIOACTIVE WATER NAFTUSSYA FROM LAYERS TRUSKAVETS’, POMYARKY AND SKHIDNYTS’A. Communication 1. GENERIC EFFECTS Nadiya O Sydoruk1, Walery Zukow2 1JSC “Dnipro-Beskyd”, Truskavets’, Ukraine dnipro-b@bk.ru 2Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl Abstracts Background. Ukraine has a number of fields Bioactive Water Type “Naftussya” focused on the Ukrainian Carpaty: Truskavets’, Skhidnytsya, Shklo, Mrazhnytsya, Opaka, Mizun’, Selyatyn, Guta etc and Podillya: Sataniv, Husyatyn, Makiv etc. Until now conducted comparative studies of their effects only on clinical symptoms as well as excretion of urine and bile. The aim of this study – compare immediate effects of Bioactive Water Naftussya from layers Truskavets’, Pomyarky and Skhidnyts’a on neuro-endocrine-immune complex. Methods. The object of observation were 15 volunteers-men without clinical diagnose but with moderate disfunction of neuroendocrine-immune complex (disadaptation). In basal conditions and after drinking Control (distillated, filtered, well) and Bioactive Waters recorded EEG (“NeuroCom Standard”) and HRV (“Cardiolab+VSR”). In blood counted up Leukocytogram, on the basis of which determined Popovych’s Adaptation Index and Strain Index. In serum of venous blood determined content of principal adaptation Hormones: Cortisol, Testosterone and Triiodothyronine (ELISA) as well as Na+ and K+ (flaming photometry) for evaluation of Mineralocorticoide activity. Immune status evaluated on a set of I and II levels recommended by the WHO. Results. Observed cohort characterized disadaptation documented high frequentlyties of Disharmonious General Adaptation Reactions (53,7%) as well as Distress (11,1%), decreased Popovych’s Adaptation Index, plasma level of Triiodothyronine, Vagal tone, Completeness of Phagocytose, blood level of “Active”, Theophilline resistance and CD4+ T-Lymphocytes, CD16+ NK-Lymphocytes as well as IgA while increased Popovych’s Strain Index, plasma level of Cortisol, Mineralocorticoide activity, Bayevskiy’s Stress and Activity Regulatory Systems Indexes, Sympathetic tone, blood level of CD8+ T-Lymphocytes as well as IgM. By method od discriminant analysis it is detected 38 variables specific to Basal level and after 1,5 h after drink Control Waters (CW) and Bioactive Waters Naftusssya (BAWN). Discriminant variables divided on four clusters. First cluster reflects caused by BAWN reversion of activating trend after CW for 17 variables (changes in Euklidian Units relative to Basal Level makes -0,14±0,03 and +0,45±0,06 respectively) while second cluster reflects reversion of inhibiting trend for 12 variables (changes relative to Basal Level makes +0,38±0,09 and -0,20±0,07 respectively). Information about these 29 variables condensed in major canonical root (62,6% discriminant properties). Means of its makes for Basal Level (n=54) +0,05±0,13 Mahalanobis’ Units, after CW (n=15) -3,10±0,31 while after BAWN in total (n=39) +1,12±0,20, separately for layers Truskavets’ (n=12) +1,28±0,28, Pomyarky (n=12) +1,13±0,28 and Skhidnyts’a (n=15) +0,99±0,29. Third cluster reflects attenuation of activating trend for 4 variables (changes relative to Basal Level makes +0,47±0,08 and +0,25±0,02 respectively) while fourth cluster reflects reduction of inhibiting trend for 5 variables (changes relative to Basal Level makes -0,31±0,04 and -0,10±0,03 respectively). Information about these 9 variables condensed in minor canonical root (37,4% discriminant properties). Means of its makes for Basal Level +1,03±0,14, for CW -0,94±0,20, for layers Truskavets’ -1,03±0,30, Pomyarky -1,28±0,28 and Skhidnyts’a -0,93±0,30. Conclusion. Bioactive Water Naftussya from layers Truskavets’, Pomyarky and Skhidnyts’a causes approximately equal immediate effects on 29 parameters of neuro-endocrine-immune complex different from effects of Control (distillated, filtered, well) Waters. Keywords: Bioactive Water Naftussya, EEG, HRV, Cortisol, Testosterone, Triiodothyronine, Leukocytogram, Immunity.